Implementasi Prinsip-Prinsip Etika Klasik Jus In Bello dalam Hukum Humaniter Internasional 2022-2025: Studi Kasus Konflik Rusia-Ukraina dan Israel-Palestina - Dwi Atmojo; Ranto Ucok Panggabean; Tarsisius Susilo; Benny Limbong; Agus Soeprianto (CV Rewang Rencang, 2025)
This research evaluates the interpretation and implementation of the principles of jus in bello: distinction, proportionality, military necessity, and precaution in the Russia–Ukraine and Israel–Palestine conflicts. The analysis results reveal the frequent violations of the principles of distinction and proportionality due to claims of strategic necessity, as well as the failure of precautionary measures in minimizing civilian casualties. Although the enforcement framework of IHL through the UN, ICJ, and ICC is strong normatively, its effectiveness is hindered by politics and resources. In conclusion, the enforcement of jus in bello requires more effective international coordination, clear new weapon regulations, and the cultivation of HHI compliance among the military.